Vaccination coverage, hesitancy and associated factors: a household survey of a cohort of children born in 2017 and 2018 in urban areas of state capital cities in the Brazilian Northeast - Ramon da Costa Saavedra; Martha Suely Itaparica de Carvalho Santiago; Maria da Glória Lima Cruz Teixeira; Maria Bernadete de Cerqueira Antunes; Rejane Christine de Sousa Queiroz; Luisa Helena de Oliveira Lima; Alberto Novaes Ramos Jr; Anderson Fuentes Ferreira; Adjoane Mauricio Silva Maciel; Jaqueline Caracas Barbosa; Ana Paula França; Carla Magda Allan Santos Domingues; et al. (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To estimate vaccination coverage and analyze sociodemographic factors associated with non-vaccination in children born in 2017 and 2018 in the state capitals of Northeast Brazil. Methods A household survey using cluster sampling was conducted from 2020-2022 to estimate vaccination coverage and hesitancy. Factors associated with non-vaccination were analyzed using logistic regression to calculate Odds Ratios (OR) and their Confidence Intervals (95%CI). Results Natal was the capital with the lowest vaccination coverage, below 75.0% for most immunizers. Teresina had rates equal to or greater than 90.0% for all vaccines. Among those interviewed, 99.1% (95%CI 98.9;99.3) believe that vaccines are important for health; 95.4% (95%CI 95.0;95.8) trust immunobiologicals and 79.6% (95%CI% 78.8;80.3) are not afraid of reactions. Belonging to the highest socioeconomic stratum (adjusted OR: 1.34 - 95%CI 1.20;1.50) was as a factor associated with non-vaccination. Conclusion Low coverage highlights the need for a better understanding of regional specificities and social inequalities.